KOMODITAS KEDELAI DALAM HEGEMONI EKONOMI NEOLIBERALISME (Studi Kasus Tata Produksi dan Tata Niaga Kedelai di Kabupaten Grobogan, Jawa Tengah) - Sitaresmi, Cike (Politika: Jurnal Ilmu Politik, 2015)
Neoliberalism has been secured through the policies of the Bretton Woods institutions , the IMF ,the World Bank and the World Trade Organization (WTO).  Hegemony economic and political factors produced the emergence of a neoliberal regime with a predatory capitalist oligarchy playing an ever greater role in Indonesian agriculture,especially soybean comodity. This thesis also describes the relationship of agricultural policy with the soybean self-sufficiency in terms of the flood of imported soybeans. . This research using qualitative methods,  writer take the location of research in Grobogan Regency as a representation of the neoliberal economic hegemony in soybean commodity. Grobogan Regency  known as the center of soybean production in  Central Java but in fact  Grobogan Regency is  not self-sufficient in soybeans and fall in the soybean imports trapped. Keywords: neoliberalism , hegemony, soybean commodity, self sufficient